2015
DOI: 10.1038/ncomms9579
|View full text |Cite
|
Sign up to set email alerts
|

Exciton–polaritons in van der Waals heterostructures embedded in tunable microcavities

Abstract: Layered materials can be assembled vertically to fabricate a new class of van der Waals heterostructures a few atomic layers thick, compatible with a wide range of substrates and optoelectronic device geometries, enabling new strategies for control of light–matter coupling. Here, we incorporate molybdenum diselenide/hexagonal boron nitride (MoSe2/hBN) quantum wells in a tunable optical microcavity. Part-light–part-matter polariton eigenstates are observed as a result of the strong coupling between MoSe2 excito… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
418
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 446 publications
(436 citation statements)
references
References 58 publications
17
418
1
Order By: Relevance
“…We find that the broadened line shapes are reasonably well fit by dispersive Lorentzians, allowing us to compare the dependence of maximal extinction on total exciton linewidth γ tot to the theoretical value 1 − ðγ tot − ΓÞ 2 =γ 2 tot . This comparison in turn allows us to determine the radiative decay rate to be in the range 1.3 < Γ < 1.8 meV, which is in good agreement with the values previously determined from normal-mode splitting of exciton polaritons [11,12]. We remark that, at the locations yielding the highest observed extinction factor of ∼0.9, we extract consistently higher values of Γ.…”
Section: (C)supporting
confidence: 88%
See 1 more Smart Citation
“…We find that the broadened line shapes are reasonably well fit by dispersive Lorentzians, allowing us to compare the dependence of maximal extinction on total exciton linewidth γ tot to the theoretical value 1 − ðγ tot − ΓÞ 2 =γ 2 tot . This comparison in turn allows us to determine the radiative decay rate to be in the range 1.3 < Γ < 1.8 meV, which is in good agreement with the values previously determined from normal-mode splitting of exciton polaritons [11,12]. We remark that, at the locations yielding the highest observed extinction factor of ∼0.9, we extract consistently higher values of Γ.…”
Section: (C)supporting
confidence: 88%
“…Encapsulation of TMD monolayers with hexagonal boron nitride (h-BN) [7,8] dramatically improves the optical quality, yielding an exciton linewidth ∼2 meV [9,10]. These narrow linewidths have a dominant contribution from radiative decay of ∼1.5 meV for MoSe 2 [11,12]. Motivated by these developments, we previously analyzed the optical response of a monolayer TMD theoretically [13] and showed that it realizes an atomically thin mirror [13][14][15].…”
mentioning
confidence: 99%
“…Strong coupling is defined by the following three important parameters [81]: g = energy transfer rate between light and matter, κ = rate of light escape from the cavity, and γ = rate of matter loses its polarization.…”
Section: Strong Exciton-plasmon Couplingmentioning
confidence: 99%
“…Exciton binding energies are about an order of magnitude higher than those of bulk semiconductors, such as Si, Ge and III-V or II-VI alloys, which allows for the direct observation of trions and biexcitons that are hard to see in bulk semiconductors. Exciton-polaritons have been recently observed in 2D materials inserted in microcavities 5,6 , although polariton condensation is still elusive.The latest group of 2D materials to be taking the stage are the so-called Xenes, where atoms from the group IVA elements are organized into a single layered, honeycomblike lattice. Contrary to flat graphene, they suffer from inherent buckling, which has a profound effect on their properties.…”
mentioning
confidence: 99%
“…Exciton binding energies are about an order of magnitude higher than those of bulk semiconductors, such as Si, Ge and III-V or II-VI alloys, which allows for the direct observation of trions and biexcitons that are hard to see in bulk semiconductors. Exciton-polaritons have been recently observed in 2D materials inserted in microcavities 5,6 , although polariton condensation is still elusive.…”
mentioning
confidence: 99%